O "efeito bumerangue" a partir das relações entre os níveis de participação dos cidadãos e suas motivações nas questões públicas - Amorim, Amanda Florense Alves (2024)
This doctoral thesis encompasses four studies that explore citizen participation, employing an interdisciplinary and varied methodological approach. Study 1 conducted a systematic review to build a framework on levels of citizen participation, mapping 33 studies and proposing a general theoretical model. Study 2, stemming from this review, presented a multidimensional model to measure levels of citizen participation in the Brazilian context, highlighting factors such as "Information," "Consultation," "Partnership," and "Delegation of Power." This model was validated through exploratory and confirmatory factor analyses, providing a robust tool for future research. Study 3 focused on measuring the participation of advisors in the Democratic Budget of Paraíba, adopting a methodological individualism approach. The quantitative and applied research revealed different levels of participation, emphasizing early stages and challenges in the dimensions of "Partnership" and "Delegation of Power." Finally, Study 4 investigated the relationship between motivation for voluntary work and citizen participation among volunteer advisors. Using a functionalist-positivist approach and scales from Cavalcante (2016) and Amorim (2023), the study found a correlation between motivations and citizenship practices, suggesting that altruistic motivations are associated with higher levels of participation. Together, these studies provide a comprehensive view of citizen participation, from systematic review and framework construction to the practical application of these models in specific contexts, such as the Democratic Budget councils of Paraíba.